Bioethics and activism: A natural fit?. (8th February 2019) - Rogers, Wendy
Abstract: Bioethics is a practically oriented discipline that developed to address pressing ethical issues arising from developments in the life sciences. Given this inherent practical bent, some form of advocacy or activism seems inherent to the nature of bioethics. However, there are potential tensions between being a bioethics activist, and academic ideals. In academic bioethics, scholarship involves reflection, rigour and the embrace of complexity and uncertainty. These values of scholarship seem to be in tension with being an activist, which requires pragmatism, simplicity, certainty and, above all, action. In this paper I explore this apparent dichotomy, using the case example of my own involvement in international efforts to end forced organ harvesting from prisoners of conscience in China. I conclude that these tensions can be managed and that academic bioethics requires a willingness to be activist.